Hyers–Ulam Stability Results for a Functional Inequality of s,t-Type in Banach Spaces - Raweerote Suparatulatorn; Tanadon Chaobankoh (Journal of Function Spaces)
We introduce an additive s,t-functional inequality where s and t are nonzero complex numbers with 2s+t<1. Using the direct method and the fixed point method, we give the Hyers–Ulam stability of such functional inequality in Banach spaces.